If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 8) = 24 + 3x Reorder the terms: 3(8 + x) = 24 + 3x (8 * 3 + x * 3) = 24 + 3x (24 + 3x) = 24 + 3x Add '-24' to each side of the equation. 24 + -24 + 3x = 24 + -24 + 3x Combine like terms: 24 + -24 = 0 0 + 3x = 24 + -24 + 3x 3x = 24 + -24 + 3x Combine like terms: 24 + -24 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -8-6q=-5q-10 | | X^2-250/x | | -3j+9=-5j-7 | | 2+f=f-1 | | 1/3x^4-2x^3 | | 10p+2=2+10p | | -10-3h=-3h-10 | | 7/5a=-14/3 | | -3+3r=10+3r | | -8w=-5-9w | | -2t+5= | | -24.226674+0.1x=-1.93(1-4.2x) | | 10-x+y+10=40 | | -12+12x-3x^2=0 | | 2x^2+x=420 | | (9/4y)^3*y^2 | | 3/16(x)=150 | | 3/16x=150 | | -3/8u=18 | | 25000-1200y=x | | 6(2x+4)=2(3x+6) | | 6(2+4)=2(3x+6) | | 6(2+4)=(3x+6) | | 1.49(w-4.3)=14.82 | | (5-w)(4w-1)=0 | | 9w+27=6(w+6) | | 10.59=12.7g-3.45-7.3g | | 29.03=3.5c+7.19 | | 14=67y-49/30 | | x^8-x^4-6=0 | | 4.36(v+8.27)=47.96 | | 2.6(x+1.8)=14.82 |